Spitting in the soup: disain intervensi dalam konseling untuk mereduksi perilaku maladaptif pada remaja - Devi Ratnasari (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
Against a variety of events that indicate a lot of maladaptive behavior by teenagers, this article aims to provide insight into the use of the